Interlayer spacing in pillared and grafted MCM-22 type silicas: density functional theory analysis versus experiment. Issue 6 (26th October 2022) - Han, Yong; Chatterjee, Puranjan; Alam, Sardar B.; Prozorov, Tanya; Slowing, Igor I.; Evans, James W.
Abstract : Density functional theory predicts that adding a succinic anhydride type pillaring agent to a pure silica precursor MCM-22P produces pillared or grafted MCM-22 type silicas with interlayer spacing 2.0 to 2.5 Å greater than the MCM-22 molecular sieve. Abstract : Pillaring of synthetic layered crystalline silicates and aluminosilicates provides a strategy to enhance their adsorption and separation performance, and can facilitate the understanding of such behavior in more complex natural clays. We perform the first-principles density functional theory calculations for the pillaring of the pure silica polymorph of an MCM-22 type molecular sieve. Starting with a precursor material MCM-22P with fully hydroxylated layers, a pillaring agent, (EtO)3 SiR, can react with hydroxyl groups (–OH) on adjacent internal surfaces, 2(–OH) + (EtO)3 SiR + H2 O → (–O)2 SiOHR + 3EtOH, to form a pillar bridging these surfaces, or with a single hydroxyl, –OH + (EtO)3 SiR + 2H2 O → (–O)Si(OH)2 R + 3EtOH, grafting to one surface. For computational efficiency, we replace the experimental organic ligand, R, by a methyl group. We find that the interlayer spacing in MCM-22 is reduced by 2.66 Å relative to weakly bound layers in the precursor MCM-22P. Including (–O)2 SiR bridges for 50% (100%) of the hydroxyl sites in MCM-22P increases the interlayer spacing relative to MCM-22 by 2.52 Å (2.46 Å). For comparison, we also analyze the system where all –OH groups in MCM-22P are replaced by non-bridging grafted (–O)Si(OH)2 R which results in a smaller interlayer spacing expansion of 2.17 Å relative to MCM-22. Our results for the interlayer spacing in the pillared materials are compatible with experimental observations for a similar MCM-22 type material with low Al content (Si : Al = 51 : 1) of an expansion relative to MCM-22 of roughly 2.8 Å and 2.5 Å from our x-ray diffraction and scanning transmission electron microscopy analyses, respectively. The latter analysis reveals significant variation in individual layer spacings.